2015
DOI: 10.1093/mnras/stv467
|View full text |Cite
|
Sign up to set email alerts
|

The behaviour of dark matter associated with four bright cluster galaxies in the 10 kpc core of Abell 3827

Abstract: Galaxy cluster Abell 3827 hosts the stellar remnants of four almost equally bright elliptical galaxies within a core of radius 10 kpc. Such corrugation of the stellar distribution is very rare, and suggests recent formation by several simultaneous mergers. We map the distribution of associated dark matter, using new Hubble Space Telescope imaging and VLT/MUSE integral field spectroscopy of a gravitationally lensed system threaded through the cluster core. We find that each of the central galaxies retains a dar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
189
4

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(205 citation statements)
references
References 82 publications
(105 reference statements)
11
189
4
Order By: Relevance
“…This model of dark matter is supported by numerous astrophysical observations [36][37][38][39][40] and other experimental data related to the muon anomalous magnetic moment [41] and experimental searching for the 'dark photon' [42][43][44][45][46].…”
Section: Jhep03(2016)215supporting
confidence: 55%
“…This model of dark matter is supported by numerous astrophysical observations [36][37][38][39][40] and other experimental data related to the muon anomalous magnetic moment [41] and experimental searching for the 'dark photon' [42][43][44][45][46].…”
Section: Jhep03(2016)215supporting
confidence: 55%
“…Cluster mergers have been used by many studies to constrain SIDM (see e.g., Randall et al 2008;Dawson et al 2012;Kahlhoefer et al 2014;Massey et al 2015;Schaller et al 2015;Kim et al 2017;Robertson et al 2017), with typical limits of m 1 cm g 2 1  s -on the self-interaction cross-section. However, recent work by Kim et al (2017) showed that constraints based on the displacement of the stellar and DM centroids are overly stringent, weakening previous constraints.…”
Section: Properties Of Viable Sidm Modelsmentioning
confidence: 99%
“…However in Ref. [30], the authors estimated the DM self-interaction cross section needed to reproduce the observed effects, and argued that the sensitivity of Abell 3827 has been significantly overestimated in a previous study [31]. In fact, their basic point was that the model used in Ref.…”
Section: Comparison Of Coillisionless λCdm Model Simulations (Left mentioning
confidence: 97%
“…In fact, their basic point was that the model used in Ref. [31] to interpret the observations in terms of DM self interactions failed to take into account the non independent development of the stars and the DM subhalo due to the initial gravitational bound of the former to the latter. Indeed, to achieve a star-subhalo separation, as observed, one would need external forces (such as self interactions) comparable in strength to the gravitational attraction within the system.…”
Section: Comparison Of Coillisionless λCdm Model Simulations (Left mentioning
confidence: 99%